HERMENEUTIKA DALAM STUDI ALQURAN: Analisis Pemikiran Hamid Fahmy Zarkasyi - Deybi Agustin Tangahu (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2017)
Hermeneutics as a method of interpretation is still a controversial debate among Muslim intellectuals, especially its application in the study of the Qur'an. A method that is a contribution of Western scholars is considered by some circles of thinkers can be an alternative and guarantee in understanding and reveal the intent behind the text of a verse. However, according to Hamid Fahmy Zarkasyi one of the leaders of ISTAC, hermeneutics is a threat to Islamic thought and civilization , even as a conspiratorial agent of the West over Islam. He saw three things that influence hermeneutics as an interpretative theory namely, first, from Greek mythology to Jewish and Christian theology. Second, from a problematic Christian theology to the rationalization and philosophy movement. Third, from philosophical hermeneutics to hermeneutic philosophy. Based on these three things, according to Hamid Fahmy, hermeneutics is full of values ​​and